DIGLOSIA OPTIMIZATION ANALYSIS OF SPEAKING SKILLS FOR EXPOSING OPINIONS IN CLASS 3 AT SDN BANJARAN - Siti Papat Patimah; Nurul Mahmudah; Ichsan Fauzi Rachman (Media Inovasi Pendidikan dan Publikasi, 2024)
This research departs from the hypothesis that there is a positive influence of diglossia on the ability to express opinions in grade 3 elementary school students. This research aims to reveal the use of two language variations, namely high language variety (T) and low language variety (R) and their influence on speaking abilities, especially in expressing opinions to children. This research uses a qualitative method approach to determine the process of optimizing the influence of diglossia on education. Data collection techniques use library research, reading, processing and data techniques. The results obtained show that students who integrate diglossia in Indonesian language learning, especially the ability to express opinions, show greater biliteracy and increased cognitive flexibility than students who receive monolingual education in general. Combining these two varieties of language can also foster a better understanding of cultural tropes and customs. This research advances knowledge about the educational potential of diglossia and opens the door to the creation of pedagogical strategies that maximize its benefits for learning excellence and student development in expressing insightful and culturally competent opinions.